Reconstruction of Notary examination mechanism as a witness in the investigation phase after the Constitutional Court decision Number 49 / PUU-X/2012 - Bustani, Bustani (Ipso Jure, 2026)
The position of the Notary as a public official who is authorized to make authentic deeds places him in a strategic position in the civil law proof system as well as in the criminal law enforcement process. In practice, it is not uncommon for a notary to be called and checked at the stage of the investigation regarding the deed drawn up by him. This study aims to analyze the concept of notary position in the investigation process as well as the mechanism of summoning and examination of notaries as witnesses after the decision of the Constitutional Court decision Number 49/PUU-X/2012. The method used is normative legal research with a legislative and conceptual approach, especially to the Notary Office Act and the Code of Criminal Procedure. The results showed that notaries can be called as witnesses, experts, or related parties, but still bound by the obligation to maintain the confidentiality of the position. After the Constitutional Court decision, the mechanism for calling notaries must still pay attention to the principle of protecting positions through special procedures as stipulated in Article 66 of the UUJN. Therefore, a balance is needed between the authority of investigators in uncovering criminal acts and the protection of the dignity and independence of the notary profession in order to ensure certainty, justice, and legal expediency.